Analysis of criminal responsibility for the crime of premeditated murder: An analysis of decision number 813K/Pid/2023 - Armelia, Dea; Rosikhu, Muhammad; Rahmatyar, Ana (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: This research is motivated by the existence of premeditate murder where the suspect is a member of the police force, namely Ferdy Sambo, the motive for this murder is heartbreak towards the victim who is suspected of committing sexual harassment against Ferdy Sambo’S wife, Putri Candrawati, the problems that arise regarding the regulation of criminal liability for premeditated murder and the application of criminal sanctions for premeditated. Methods: The type of research used by the author is the normative legal and juridical. Statuta Approach, Case Approach, Comparative Approach. Findings: That the act of premeditated murder is regulated in Article 340 of the Criminal Code with a maximum penalty of 20 years imprisonment, while in Law No 1 of 2023 or the National Criminal Code the crime of premeditated murder is regulated in article 459 with the same penalty but the difference is the death penalty embedded in Article 100 of Law No. 1 of 2023 which with a probationary period of 10 years in prison if good behaviour can be changed to life. Conclusion: The use of Law No. 1 of 2023, which should take effect only 3 years later in accordance with Article 624 of Law No. 1 of 2023, it is necessary to review the decision of the Supreme Court on the use of the National Criminal Code as a consideration for the decision in the case of the defendant Ferdy Sambo and also the defendant Ferdy Sambo received a reduction in sentence which was. Novelty/Originality of this Study: This study provides a critical analysis of the application of Law No. 1 of 2023 concerning the Criminal Code in the case of Ferdy Sambo, particularly examining the shift from retributive to rehabilitative criminal justice paradigms. It uniquely highlights the implications of implementing future legislation in current judicial decisions, questioning the appropriateness and legality of such premature application.